PENENTUAN PRIORITAS PADA JARINGAN BACK-BONE PALAPA RING MENGGUNAKAN DERAJAT NODE DAN CUT VERTEX - Stephanie Imelda Pella; Hendro FJ Lami (Universitas Nusa Cendana, 2019)
Palapa Ring is a project aiming to connect provinces and cities in Indonesia via a high data speed telecommunication path. The purpose of this research is to identify the priority scale of each node in Palapa Ring Backbone network by considering the degree of each node and the cut vertices of the network. The result shows that the existing infrastructure in Palapa Ring comprised 48 nodes and 117 links. The nodes with the highest degree in the network were PBR, PTK, BJM, JK, SB and UP, with each of the nodes was connected to four links. Cut vertices in the network consisted of 22 nodes. The nodes in the network are classified into 4 categories. Five nodes (PBR, PTK, BJM, SB and UP) fell into the 1st priority group, two nodes (JK,MDN) fell into the 2nd priority group, 16 nodes fell into the 3rd priority group and the rest fell into the non priority group.